Farmers’ Perception on Acceptability of Improved Sugarcane Varieties in Kakamega County, Kenya - Thuo, Caroline Muthoni; Nkurumwa, Dr.Agnes Oywayo (Advances in Social Sciences Research Journal, 2019)
Improved sugarcane varieties have been developed and promoted in Kenya, with an aim of enhancing sugarcane productivity. However, their acceptance by farmers is low. This paper examines farmers’ perception on these varieties as a basis for explaining their acceptability by farmers and attempts to underpin determinants that inhibit or facilitate their acceptance. This study was conducted using a cross-sectional survey research design. Target population was 137,355 small-scale sugarcane farmers from Kakamega County, from which a sample of 384 farmers was randomly selected. Questionnaires were used to collect data, which was analyzed using descriptive and inferential statistics. The research findings confirmed that majority of farmers produced old commercial sugarcane varieties. Respondent farmers prioritized high tonnage, early maturity, pest resistance, ratoonability, high tillering and disease resistance as the top preferred attributes of sugarcane varieties. Based on the farmers’ perception, an association between farmers preferred sugarcane attributes and acceptability of the improved sugarcane varieties was established. Improved sugarcane varieties that portrayed compatible attributes with farmers’ preferred traditional varieties were found to be highly acceptable for production by farmers. Compatibility of improved sugarcane technologies with the farmers’ perceived needs, preferences and values therefore need to be considered in the development of improved sugarcane technologies to enhance their appropriateness and acceptance by farmers. Findings from this study would avail critical information in sugarcane research and development which may serve as a guide to technology developers to ensure technologies produced meet preferences of the targeted user for enhanced technology acceptance.